2022
DOI: 10.3390/ma15196762
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Surface Treatment Process of AISI 304 Stainless Steel by Centrifugal Disc Finishing with the Use of an Active Workpiece Holder

Abstract: This article presents the results of experimental studies of the centrifugal disc finishing (CDF) process of 304 steel elements with the use of an active workpieces holder, that allows workpieces for additional rotational and oscillation movements. The main aim of the research was to evaluate the mechanism of formation of the surface texture and to assess the intensity and effectiveness of the machining process. It is shown that additional movements of the workpiece significantly affect the formation of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…An increase in the material removal rate is observed for the rotary oscillation movement of the workpiece. Better surface roughness is also achieved by this process due to the increased frequency of contact of the workpiece with the abrasive [7]. The vibration-assisted finishing process has also been utilized for microfinishing of magnesium alloy parts using a vertical vibration-assisted magnetic abrasive process.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the material removal rate is observed for the rotary oscillation movement of the workpiece. Better surface roughness is also achieved by this process due to the increased frequency of contact of the workpiece with the abrasive [7]. The vibration-assisted finishing process has also been utilized for microfinishing of magnesium alloy parts using a vertical vibration-assisted magnetic abrasive process.…”
Section: Introductionmentioning
confidence: 99%
“…This process can therefore be used for finishing complex-shaped components. The BCVF approach combines the benefits of vibratory peening [2][3][4] and vibration assistance polishing [5][6][7][8] to enhance surface quality while increasing machining efficiency. However, the insightful quantitative understanding of the BCVF remains very limited, restricting its practical application.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that robotic belt grinding is more efficient in terms of quality and produces more consistent results than manual grinding. In finishing, Juniewicz, Plichta, et al [ 28 ] presented the results of experimental studies of the centrifugal disc finishing (CDF) process of steel elements with the use of an active workpiece holder that allows workpieces for additional rotational and oscillational movements. The mechanism of formation of the surface texture was evaluated, and the intensity and effectiveness of the machining process were assessed.…”
mentioning
confidence: 99%